544 Multiomic characterization of T-cell populations at the single-cell level utilizing sensitive dextramers and BD® AbSeq on the BD RhapsodyTM Single-Cell Analysis system. (9th November 2020) - Jacobsen, Kivin; Sakofsky, Cynthia; Lopez-Salmeron, Vadir; Nakamoto, Margaret; Brix, Liselotte; Mortimer, Stefanie; Jacobsen, Kivin
Abstract : Background: Adoptively transferred antigen-specific T cells have shown great efficacy in treatment of some virus-associated diseases and malignancies. A major driver of the development of adoptive T-cell therapy has been our ability to successfully characterize the functional status and antigen specificity of T cells. However, this has been limited by inefficient detection of antigen-specific T cells possibly due to their low frequency and low binding affinities to known MHC-peptide complexes. Methods: Here, we aim to combine two powerful technologies, advanced dCODE™ Dextramer® from Immudex and single-cell multiomics analysis using the BD Rhapsody™ Single-Cell Analysis system, to detect and characterize disease-specific CD8+ T cells within thousands of PBMCs. Results: Currently, we are able to identify over 350 mRNAs alongside a panel of over 20 BD® AbSeq cell surface protein markers which can be associated with T cell activation states. These data can be used to define T-cell phenotypes alongside antigen specificity of enriched CD8+ Dextramer(R)+ cells from a PBMC population. Conclusions his study outlines our ability for high-resolution T-cell profiling that has broader implications and utility in immuno-oncology, infectious diseases and autoimmunity. Acknowledgements: For Research Use Only. Not for use in diagnostic or therapeutic procedures. BD, the BD Logo, and Rhapsody are trademarks of Becton, Dickinson and Company or its affiliates. © 2019 BD. All rights reserved.